Social anxiety among trainee audiologist and speech language pathologist in Bengaluru: a cross sectional study - Babu, Praveena; Rajan, Rithu; T., Suresh; A. , Srividya (International Journal Of Community Medicine And Public Health, 2023)
Background: Audiologist and Speech language pathologist (ASLPs) are a group of professionals specialized in communication disorders. Their work responsibilities require them to be interacting with people with different backgrounds, education and ages who seek assistance from these young professionals. It is important to know whether the professionals who are meant to deal with individuals with communication disorders are themselves going through social anxiety or not. Methods: A questionnaire was prepared and was used for assessing social anxiety among trainee undergraduate and postgraduate ASLP’s. Data was collected via Google form further was analyzed using SPSS version 20.0. Results: Total 124 students participated in the study (20 males and 104 females). Cronbach’s test was administered to check the internal consistency of questionnaire. The overall questionnaire had a global alpha of 0.926 and global alphas for different scenarios of the questionnaire were 0.865 and 0.894 respectively indicating high internal consistency. The test retest stability for the total score found to be high with r =0.773and p<0.01. Social anxiety score differs significantly with respect to ‘Traumatic life events’ and ‘Age’. Conclusions: The study was able to deliver the answers to the questions of the researcher, that is, first, the study was able to assert the use of the questionnaire in the target population. Second, study found a statistically significant difference on anxiety scores between different scenarios i.e, social and professional life.